Islamic Intellectual Capital: Unveiling its Impact on Maqashid Shariah Performance under Corporate Governance Moderation - Qurrota A'yun, Annisa; Mohammed Sultan Saif, Gehad; Andriansa, Rama; Nur Rahman, Arif; Danang Saputra, Aditya; Ayu Lestari, Mey (Journal International Economic Sharia, 2024)
This study investigates the performance of Islamic banking in Indonesia by analyzing the impact of Islamic Intellectual Capital (iB-VAIC) on Maqashid Shariah performance, with corporate governance as a moderating variable. Data from annual reports of Sharia-compliant banks listed on the Indonesia Stock Exchange over the period 2019-2023 were analyzed using multiple regression analysis in SPSS. The results reveal a negative direct effect of Islamic intellectual capital and board meetings on Maqashid Shariah performance. However, the interaction between Islamic intellectual capital and board meetings positively influences performance, suggesting a moderating role of corporate governance. These findings underscore the importance of effective management of intellectual capital and governance mechanisms to enhance performance aligned with Shariah principles in Islamic banking. Further research is recommended to deepen our understanding of these relationships and inform strategic decisions in the Islamic banking sector.